Role of IL-38 and Its Related Cytokines in Inflammation - Xianli Yuan; Xiao Peng; Yan Li; Mingcai Li (Mediators of Inflammation)
Interleukin- (IL-) 38 is a recently discovered cytokine and is the tenth member of the IL-1 cytokine family. IL-38 shares structural features with IL-1 receptor antagonist (IL-1Ra) and IL-36Ra. IL-36R is the specific receptor of IL-38, a partial receptor antagonist of IL-36. IL-38 inhibits the production of T-cell cytokines IL-17 and IL-22. IL-38 also inhibits the production of IL-8 induced by IL-36γ, thus inhibiting inflammatory responses. IL-38-related cytokines, including IL-1Ra and IL-36Ra, are involved in the regulation of inflammation and immune responses. The study of IL-38 and IL-38-related cytokines might provide new insights for developing anti-inflammatory treatments in the near future.